The Impact of Institutions on Foreign Policy Think Tanks in France and Denmark. Issue 1 (2nd January 2017) - Rahbek-Clemmensen, Jon; Schmitt, Olivier
Abstract: Even though France is an active player on the world stage, its foreign and security think tank milieu is smaller than that of similar powers, most notably the United Kingdom. Comparing French think tanks with those in Denmark illustrates how French institutional structures constrain think tank activities. France's political tradition of centralisation, its non-academic civil service education, and separation of academia and administration create an environment in which think tanks are underfunded and walk a fine line between an over-controlling administration and a suspicious academia. Some French think tanks perform well in spite of these structures, which indicates that they could flourish and compete at the highest international level if given better structural conditions.